2017
DOI: 10.3390/su9071186
|View full text |Cite
|
Sign up to set email alerts
|

Tourist Satisfaction Enhancement Using Mobile QR Code Payment: An Empirical Investigation

Abstract: Innovative technologies have greatly changed people's lives, including their travel experiences. This study investigates the antecedents and outcomes of the quick response (QR) code payment technology used in tourism to provide empirical evidence that mobile technologies can be used to enhance tourist satisfaction. An empirical analysis using 247 field survey responses reveals that relative advantage, compatibility, and observability innovation attributes significantly affect tourists' attitudes positively tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 46 publications
(81 reference statements)
2
43
0
3
Order By: Relevance
“…Oliveira [19] confirmed that compatibility is the most important variable in explaining the adoption of mobile payment, and believed that if customers see the benefits of using mobile payment to perform certain activities, they may consider mobile payment to have better compatibility with their needs. In addition, previous studies have mentioned that compatibility is a vital factor affecting the adoption of mobile payment services [13,15,25,46], and have proposed that when customers discover the advantages of mobile payment and believe that mobile payment is consistent with their lifestyle, they increase their adoption of mobile payment, which also proves that compatibility has a positive impact on the users' intention to adopt mobile payment [12,20].…”
Section: Compatibilitymentioning
confidence: 96%
“…Oliveira [19] confirmed that compatibility is the most important variable in explaining the adoption of mobile payment, and believed that if customers see the benefits of using mobile payment to perform certain activities, they may consider mobile payment to have better compatibility with their needs. In addition, previous studies have mentioned that compatibility is a vital factor affecting the adoption of mobile payment services [13,15,25,46], and have proposed that when customers discover the advantages of mobile payment and believe that mobile payment is consistent with their lifestyle, they increase their adoption of mobile payment, which also proves that compatibility has a positive impact on the users' intention to adopt mobile payment [12,20].…”
Section: Compatibilitymentioning
confidence: 96%
“…Macro risks indicated risks belonging to political environment, economy, tourists' protected laws and legislations, and natural disasters. At micro levels, risks would be health risk; crime such as robbery and terrorist attacks; financial risks such as fluctuation in exchange rate, availability of credit and debit service, QR code payment (Lou, Tian, and Koh, 2017); social risk; and psychological risk.…”
Section: H2: Safety and Security Positively Affect Tourists' Satisfacmentioning
confidence: 99%
“…Zhang et al (2017) argue that online platforms enable consumers to develop more realistic travel expectations due to the co-creation of their experiences. Lou et al (2017) investigated QR code payments and found that they influence tourists' transaction and travel satisfaction. Sylejmani, Dorn, and Musliu (2017) found that IT can better obtain personalized travel itineraries for group tourists.…”
Section: Technology Enhanced Tourist Experiencesmentioning
confidence: 99%
“…The use of smartphones has altered the time and place constraints on human interaction in the travel domain (Janet E. Dickinson et al, 2014). Yet there remains little research on how tourists engage with IT such as smartphones during longer duration trips (Tan, 2017), or the use of destination online platforms (Molinillo, Liébana-Cabanillas, Anaya-Sánchez, & Buhalis, 2018;Zhang et al, 2017), or how TEIS can play a role in tourist decision making processes (Lou, Tian, & Koh, 2017). Neuhofer (2016) emphasises the significant role of IT in the value creation for tourists, and calls for further research in understanding the utility and value created through TEIS tourist experiences.…”
Section: Introductionmentioning
confidence: 99%